The Bismarck Myth : Weimar Germany and the Legacy of the Iron Chancellor. - Gerwarth, Robert (Oxford historical monographs., 2005)
Few statesmen in history have inspired the imagination of generations of Germans more than the founder of the Kaiserreich, Otto von Bismarck. The archetype of charismatic leadership, the Iron Chancellor maintained his pre-eminent position in the pantheon of Germany's political iconography for much of the twentieth century. Based on a large selection of primary sources, this book provides an insightful analysis of Bismarck's legacy as a political myth that undermined parliamentary. democracy in Germany and contributed to the rise of Hitler. - ;Few statesmen in history have inspired the imaginat.